Implementasi dan Pengembangan Kurikulum Merdeka dalam Mewujudkan Pendidikan Berkualitas - Amanulloh, Mochammad Ja'far Amri; Wasila, Nur Fathiya Warda (Lembaga Sosial Rumah Indonesia, 2024)
Purpose - The purpose of this study is to identify and analyze the implementation of the Independent Curriculum as well as the development and evaluation carried out in schools. This focus is important considering that this curriculum has only been implemented in the second year and has not been fully implemented in schools.Methods - This study uses qualitative methods with a descriptive approach that aims to describe subjects related to observed conditions and data obtained through observation, interviews, and documentation. The research was conducted at SD Negeri Sumbersari 3 Malang City. Data from observations, interviews, and document analysis can be analyzed using content analysis to identify patterns, themes, and concepts that emerge and develop them using relevant theories.Findings - The findings of this study are several obstacles in the implementation of the Merdeka curriculum at SD Negeri Sumbersari 3 Malang City, which involves internal school factors and the influence of external factors such as policies, socialization, and regulations. The lack of experience and understanding at SD Negeri 3 Sumbersari creates difficulties for teachers, especially in implementing learning differentiation, and results in orientation errors towards the Pancasila Student Profile Strengthening Project (P5).Research Implications - In this study, the author analyzes the forms and patterns of problems that occur in the field with several strategies and developments to improve existing problems based on the substance of the curriculum as a system, where the curriculum is a unity that cannot be separated between components. This research has limitations, especially in efforts to develop an independent curriculum that only focuses on aspects of the curriculum system framework. In this case, there needs to be development in other aspects.